Clostridium sordellii as a Cause of Fatal Septic Shock in a Child with Hemolytic Uremic Syndrome - Rebekah Beyers; Michael Baldwin; Sevilay Dalabih; Abdallah Dalabih (Case Reports in Pediatrics)
Clostridium sordellii is a toxin producing ubiquitous gram-positive anaerobe, mainly associated with trauma, soft tissue skin infections, and gynecologic infection. We report a unique case of a new strain of Clostridium sordellii (not present in the Center for Disease Control (CDC) database) infection induced toxic shock syndrome in a previously healthy two-year-old male with colitis-related hemolytic uremic syndrome (HUS). The patient presented with dehydration, vomiting, and bloody diarrhea. He was transferred to the pediatric critical care unit (PICU) for initiation of peritoneal dialysis (PD). Due to increased edema and intolerance of PD, he was transitioned to hemodialysis through a femoral vascular catheter. He subsequently developed severe septic shock with persistent leukocytosis and hypotension, resulting in subsequent death. Stool culture confirmed Shiga toxin producing Escherichia coli 0157:H7. A blood culture was positively identified for Clostridium sordellii. Clostridium sordelli is rarely reported in children; to our knowledge this is the first case described in a pediatric patient with HUS.